Estimating the Incidence of Road Traffic Fatalities and Injuries in Sri Lanka Using Multiple Data Sources - Bhalla, K.; Navaratne, K. V.; Shahraz, S.; Bartels, D.; Abraham, J.; Dharmaratne, S. (2012)
We used data from multiple sources to estimate the incidence of fatal and non-fatal road traffic injuries in Sri Lanka in 2005. We validated the accuracy of the data from the national traffic police by comparing with estimates based on national death registration. For estimating the incidence and patterns of non-fatal injuries, we used a nationally represented health survey (World Health Survey), and data on hospital admissions from a rural setting (Galle district). We estimate that in the year 2005, approximately 2300 people died in Sri Lanka due to road traffic crashes, approximately 300,000 were injured in non-fatal crashes and approximately 140,000 received care for their injuries at hospitals. While the road traffic death rate in Sri Lanka is low compared with other low-income countries, it has been steadily rising for several years. Although young adults are at high risk in non-fatal crashes, the elderly have the highest death rate. Pedestrians and bicyclists account for more than half of all road traffic deaths and riders of motorised two-wheelers accounted for an additional 13%. The government of Sri Lanka should act immediately to stop the needless loss of life by implementing the recommendations of the 2004 World Report on Road Traffic Injury Prevention.